Analysis of nucleic acid chaperoning by the prion protein and its inhibition by oligonucleotides - Guichard, Cécile (Oxford University Press, 2011)
Prion diseases are unique neurodegenerative illnesses associated with the conversion of the cellular prion protein (PrP(C)) into the aggregated misfolded scrapie isoform, named PrP(Sc). Recent studies on the physiological role of PrP(C) revealed that this protein has probably multiple functions, notably in cell–cell adhesion and signal transduction, and in assisting nucleic acid folding. In fact, in vitro findings indicated that the human PrP (huPrP) possesses nucleic acid binding and annealing activities, similarly to nucleic acid chaperone proteins that play essential roles in cellular DNA and RNA metabolism. Here, we show that a peptide, representing the N-terminal domain of huPrP, facilitates nucleic acid annealing by two parallel pathways nucleated through the stem termini. We also show that PrP of human or ovine origin facilitates DNA strand exchange, ribozyme-directed cleavage of an RNA template and RNA trans-splicing in a manner similar to the nucleocapsid protein of HIV-1. In an attempt to characterize inhibitors of PrP-chaperoning in vitro we discovered that the thioaptamer 5′-GACACAAGCCGA-3′ was extensively inhibiting the PrP chaperoning activities. At the same time a recently characterized methylated oligoribonucleotide inhibiting the chaperoning activity of the HIV-1 nucleocapsid protein was poorly impairing the PrP chaperoning activities.